MENINGKATKAN HASIL BELAJAR IPA ANAK TUNAGRAHITA RINGAN TENTANG SIFAT BENDA CAIR MELALUI METODE EXPERIMEN KELAS DASAR I SLB MUARO BUDI SELAYO KABUPATEN SOLOK - Rosalena, Markis Yunus, Ardisal (Universitas Negeri Padang, 2013)
he research was motivated by the lack of interest and the low value of mental retardation in children, especially in science lessons explaining the nature of the liquid indicators for child mental retardation. This is because the methods used by teachers varied less given to the child at the time of learning so that children are not interested in teaching and learning process. Researchers with collaborators IPA seeks to improve outcomes for children mild mental retardation through experiments in the hope students are motivated to learn and there is an increase in the value of student learning outcomes. In accordance with the problems that will be studied and the expected information, this research aims to improve science learning outcomes of students through the basic method in class experiments I Tunagrahita. The approach used in this study is action research (Classroom Action Research). The study was conducted with berkolabori with peers, with research procedures conducted four phases: preparation,. implementation phase of research, observation and reflection stages Through experimental method tunagrahita student learning outcomes in subjects increased liquid properties. This can be seen in the first cycle AI students obtain a score of 16. While students Fj got a score of 12. In the first cycle, the percentage can be taken as follows. AI percentage of student learning outcomes are: 16/30 x 100-53%. Percentage of student learning outcomes Fj is - 12/30 x 100 = 40%. The results obtained after the second cycle of doing 30 questions given AI students can answer the questions correctly as many as 27 points and Fj students can work on the problems as much as 22 points. In cycle II can be taken to the percentage of student learning outcomes after AI using the experimental method = 24/30 x 100 = 80% .. Percentage of student learning outcomes through the experimental method Fj = 22/30 x 100 = 73.3%. Based on the findings of action research in SLB Muaro Selayo Budi. Solok Basic C class I with this it can be concluded that the ability to learn about the properties of liquid IPA can be enhanced through experimental methods. All students are achieving good grades and can work actively as well as obtain the value above the standard completeness.